Preparation and characterization of Co mordenite coatings onto cordierite monoliths as structured catalysts - Ulla, Maria Alicia del H. (2008)
Mordenite coatings onto the walls of cordierite monoliths were obtained by hydrothermal synthesis followed by cationic exchange. A battery of characterization techniques was used to describe the structured catalyst so obtained, and selective catalytic reduction (SCR) of NO with CH4 in excess O2 was used as a reaction test. A homogeneous distribution of the different components on the synthesized mordenite layer was obtained, with a Si/Al ratio lower than that of synthesis gel, suggesting aluminium transference from the substrate to the zeolite during the synthesis procedure; however, this effect was not observed for Mg. TPR results indicated that Co species in mordenite were exchanged Co2+, highly dispersed CoOx, and hydroxo-Co with a small contribution of Co3O4. The existence of different Co2+ sites is supported by NO desorption tests. Catalytic performance was fairly comparable to that of powdered Co-mordenite.